2007
DOI: 10.1259/bjr/79800547
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of radiotherapy in plantar fasciitis

Abstract: Plantar fasciitis is a common painful syndrome that is usually treated by irradiation with a fraction dose (fd) of 1 Gy up to a total dose (TD) of 6 Gy according to clinical experience. By analysing our experiences with numerous former patients, we have attempted to find the relationship between dose and effect. To evaluate the effectiveness of radiotherapy and assess the impact of fd and TD in plantar fasciitis radiotherapy, we assessed 1624 irradiations (856 patients) performed using a fd of 1-3 Gy and a TD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…However, other studies found no influence of this patient characteristic on treatment outcome [24,30,39].…”
Section: Patients' Agementioning
confidence: 81%
See 1 more Smart Citation
“…However, other studies found no influence of this patient characteristic on treatment outcome [24,30,39].…”
Section: Patients' Agementioning
confidence: 81%
“…To the best of our knowledge, in no study, an influence of gender on treatment outcome has been confirmed [22,24,30,38,39]. In contrast to radiotherapy for oncological indications with high doses, efficacy and tolerability of LD-EBRT seems to be the same concerning gender.…”
Section: Gendermentioning
confidence: 83%
“…Low dose radiotherapy (3-12 Gy) represents an effective treatment in the majority of examined patients and side effects are negligible: Miszczyk et al [29], affirm that there are no side effects, neither acute nor delayed. Therefore, radiotherapy may be considered as a possible treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a placebo effect cannot be totally excluded [12]. In according to literature, Miszczyk et al [29] considered that there are no acute or late toxicity in cases of plantar fasciitis patient irradiation [24,30,31]. Surenkok et al [32] valued a low risk of secondary cancer after irradiation therapy, and conclude that radiotherapy is an effective therapy solution for relieving pain in calcaneal spur patients.…”
Section: Radiotherapymentioning
confidence: 99%
“…The interventions are diverse and range from a simple heel pad to radiotherapy (Miszczyk et al, 2007). Autologous platelet injections is a relatively recent procedure used to reverse the degenerative process of neovascularisation diagnosis of tendinosis (Peerbooms et al, 2010).…”
Section: Pathomechanical Hypothesesmentioning
confidence: 99%